2018
DOI: 10.1111/andr.12511
|View full text |Cite
|
Sign up to set email alerts
|

A global view of the pathophysiology of varicocele

Abstract: Varicocele is the most common abnormality identified in men being evaluated for subfertility. In this comprehensive review of the pathophysiology of varicocele, we will shed light on novel pathophysiological findings and their clinical implications that may direct future researches; we will shed light on the impact of transient scrotal hyperthermia and the roles of inflammation and differential protein expression and androgen expression in spermatozoa on inducing pathophysiological findings. Furthermore, we wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 82 publications
3
64
0
18
Order By: Relevance
“…This resulted in a decrease of the cell antioxidant capacity [18,38,39]. In addition, testicular hyperthermia associated with VCL also contributes to shift the AO/ROS balance towards oxidative stress [20,40]. We are here in total agreement with the literature since we have observed that in the VCL group, all the major primary AO activities (SOD, CAT & GPX) were reduced and that the tissue MDA content was significantly increased signing a clear state of oxidative stress.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This resulted in a decrease of the cell antioxidant capacity [18,38,39]. In addition, testicular hyperthermia associated with VCL also contributes to shift the AO/ROS balance towards oxidative stress [20,40]. We are here in total agreement with the literature since we have observed that in the VCL group, all the major primary AO activities (SOD, CAT & GPX) were reduced and that the tissue MDA content was significantly increased signing a clear state of oxidative stress.…”
supporting
confidence: 86%
“…Since oxidative stress, heat stress, and hypoxia are the main factors involved not only in the pathophysiology of varicocele [20] but also in the induction of autophagy [21,22], we have sought to understand the relationship between autophagy and varicocele. The aim of this study was to create an experimental model of varicocele in rats to highlight the role of autophagy in VCL testicular tissue and sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Another situation in which raised intratesticular temperature is evident is varicocele. This condition is also known to be associated with a loss of sperm function and DNA integrity as a consequence of oxidative stress [100,101]. Surgical ligation of the left internal spermatic vein to correct the varicosity has been shown to reduce oxidative stress parameters and to improve sperm quality and the concomitant administration of antioxidants has been shown to facilitate this process [102,103].…”
Section: Lifestyle Exposuresmentioning
confidence: 99%
“…[4] Bu mekanizmalar; hipertermi, hipoksi, toksik sürrenal metabolitlerin reflüsü, hipogonadizm ve kadmium birikmesi olarak bildirilmektedir. [4,5] Ancak, bu patofizyolojik mekanizmaların hangi moleküler ve alt etkileşim mekanizmalar ile etkili olduğu halen araştırma konularıdır. [5] Güncel olarak varikoselin infertilite üzerine patofizyolojik etkisi çeşitli etyolojik faktörlerin kombine etkileşimi ile ortaya çıkmaktadır.…”
Section: öZunclassified